Analisis Simple Cell, Twin Cell, dan Tripple Cell Box Culvert Menggunakan Software Ansys - Hanifah Zahra (Jurnal Syntax Admiration, 2023)
Box culverts are part of a low-rise structure used to convey water in appropriate channels at railroad crossings, flyovers, roads and bridges. The use of box culverts is according to their function, the amount of damage to box culverts is wrong because the functions and loads that can hold the box culverts are also not taken into account. Any force given to the load affects the behavior of the structure contained in the box culvert. IRC is a loading determination that will be given to the box culvert to see the worst structural behavior that occurs. 2D and 3D modeling was carried out using SAP2000 and Ansys Workbench software with the dimensions of the box culvert model measuring 1000 x 1000 x 160 mm and 3 types, namely single box culvert, double box culvert and triple box culvert. The loading on the box culvert is in the form of a divided and evenly distributed load with a loading value in accordance with the provisions of IRC Class A. The box culvert modeling has a quality of 35 MPa and is designed with several types of loading placement on a single box culvert, double box culvert and triple box culvert structure. culvert with an evenly distributed load of 0.205 mm at maximum loading and a maximum moment of 41.988 KN, under maximum loading conditions planned support reinforcement 17D16-250 and 5D16-250 and stirrups D13-250.